A Graph-Based Handover Scheduling for Heterogeneous Vehicular Networks - Made Harta Dwijaksara; Wha Sook Jeon; Dong Geun Jeong (IEEE Access, 2018)
The vehicular networks exploiting WiFi have a great advantage in cost and capacity in comparison with the networks using cellular systems. However, to use WiFi in the vehicular environments, the problem of frequent handover (HO) due to the small coverage of access points (APs) should be resolved. In this paper, we propose a new HO technique which is effective in heterogeneous (WiFi/cellular) networks on a real road topology. Specifically, we propose an HO scheduling scheme running on a server, which determines the AP to which a user will be handed over, considering the road topology. Since a user only needs to decide when to initiate the connection to the next AP, a very fast and efficient HO in the vehicular environment can be realized. The design objective of the proposed HO scheduling is to maximize the connection time on WiFi while minimizing the total HO latency and reducing the number of users which contend for the channel within an AP. We show that this objective is well-accomplished with the proposed scheme, by using computer simulation.